Investigating the Factors that Influence the Energy Consumption of Buildings at Isabela State University in Cabagan, Isabela - Geraldine J. Paguigan, Daniel C. Jacinto (International Journal of Advanced Science and Technology, 2020)
The study focused on the energy consumption of the six buildings at Isabela State University, Cabagan Campus, in the province of Isabela, Philippines. As revealed in the survey, there is an increasing trend in energy consumption on the campus. At the same time, there was a change in the Climatological conditions such as temperature, rainfall quantity, and percentage of relative humidity on the study site. The monthly energy consumption and climatological factors using Pearson Correlation analysis revealed that temperature is highly significant at the 0.01 level. The characteristic of the buildings in terms of the number of floor level, floor area, number of occupants, lighting fixtures, and appliances used for cooling and ventilation were used to determine other factors that may influence the energy consumption of a building. The result of the correlation analysis found that the number of occupants and electrical fixtures, which includes the appliances for cooling and ventilation in the building, are the factors that were highly significant at 0.01 level. The number of floor levels of the building revealed an inverse significance at 0.01 level.